Weight Management Programme for Overweight and Obese Adults in Ningbo, China: A Feasibility Pre- and Post-intervention Study - Miao Xu; Kaushik Chattopadhyay; Jialin Li; Nanin Rai; Yanshu Chen; Fangfang Hu; Jianping Chu; Li Li (Frontiers Media S.A., 2019)
Objective: To investigate the feasibility of conducting a randomized controlled trial (RCT) of a weight management programme in Ningbo, China.Methods: A pre- and post-intervention study was conducted in Ningbo. The study duration was from 01 July 2015 to 30 September 2017. Those aged 18-65 years of age, with a body mass index (BMI) of ≥24 kg/m2 (i.e., overweight/obese) and were willing to comply with the weight management programme were included in the study. The programme, focusing on lifestyle modification, was delivered by a multidisciplinary team over a period of 3-months. The study parameters were recruitment rate, follow-up rates at 3- and 6-month and standard deviation (SD) of the outcome measure (i.e., BMI).Results: Out of 261 people who gave written informed consent and were screened for eligibility, 193 (74%) were found eligible and were enrolled on to the programme. Those who enrolled on to the programme, 185 (96%) and 169 (88%) were followed up at 3- and 6-month, respectively. The SD of the outcome measure was 4.85. BMI reduced at 3-month follow-up (−1.98, 95% CI −2.19 to −1.79, p < 0.001) and at 6-month follow-up (−2.42, −2.71 to −2.11, <0.001).Conclusion: Based on the promising recruitment and follow-up rates in this study, it would be feasible to undertake the RCT of the weight management programme for overweight and obese adults in Ningbo. The SD of the outcome measure is used to calculate the sample size of the RCT.Clinical Trial Registration:www.ClinicalTrials.gov, identifier: ChiCTR1900025861.